Magnitude and factors associated with intimate partner violence in mainland Tanzania - Method R. Kazaura; Mangi J. Ezekiel; Dereck Chitama (BMC, 2016)
Abstract Background In Tanzania like in many sub-Saharan countries the data about Intimate Partner Violence (IPV) are scarce and diverse. This study aims to determine the magnitude of IPV and associated factors among ever partnered women in urban mainland Tanzania. Methods Data for this report were extracted from a big quasi-experimental survey that was used to evaluate MAP (MAP - Men as Partners) project. Data were collected using standard questions as those in big surveys like Demographic and Health Surveys. Data analyses involved descriptive statistics to characterize IPV. Associations between IPV and selected variables were based on Chi-square test and we used binary logistic regression to assess factors associated with women's perpetration to physical IPV and Odds Ratio (OR) as outcome measures with their 95 % confidence intervals (CI). Results The lifetime exposure to IPV was 65 % among ever-married or ever-partnered women with 34, 18 and 21 % reporting current emotional, physical and sexual violence respectively. Seven percent of women reported having ever physically abused partners. The prevalence of women perpetration to physical IPV was above 10 % regardless to their exposure to emotional, physical or sexual IPV. Conclusions IPV towards women in this study was high. Although rates are low, there is some evidence to suggest that women may also perpetrate IPV against their partners. Based on hypothesis of IPV and HIV co-existence, there should be strategies to address the problem of IPV especially among women.